Republic of Nauru : 2017 Article IV Consultation- Press Release; Staff Report; and Statement by the Executive Director for the Republic of Nauru. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights Nauru's growth and a substantial improvement in government revenue in recent years thanks to processing of asylum seekers by the Australian Regional Processing Center (RPC), fishing license fees, and residual phosphate mining. In the near term, GDP growth is projected to be moderate at 4 percent in fiscal year 2017 (ending June 30) mainly due to a slowdown in phosphate exports and limited expansion of the RPC. The medium-term outlook is vulnerable to scaling down of the RPC following the expected transfer of refugees to other countries, which will produce a substantial decline in RPC revenue.